2001
DOI: 10.1007/s15010-001-1028-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Clarithromycin in Preventing Viridans Streptococcal Bacteremia following autologous Stem Cell Transplantation

Abstract: Age, duration of neutropenia, type of underlying malignancy and type of conditioning chemotherapy regimen failed to have a significant impact on subsequent VS bacteremia. Only female sex and use of ciprofloxacin without clarithromycin as antimicrobiaL prophyLaxis predicted a significantly increased risk of VS bacteremia in both univariate and Logistic regression analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Because the problem of clinically required ventilation period was not involved, only rate analysis was performed [23][24][25]. We found that patients with acute myelogenous leukemia had a higher fever rate but their fever occurred later.…”
Section: Discussionmentioning
confidence: 99%